2023
DOI: 10.1101/2023.02.28.529447
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A scalable, GMP-compatible, autologous organotypic cell therapy for Dystrophic Epidermolysis Bullosa

Abstract: SummaryBackgroundGene editing in induced pluripotent stem (iPS) cells has been hailed to enable new cell therapies for various monogenetic diseases including dystrophic epidermolysis bullosa (DEB). However, manufacturing, efficacy and safety roadblocks have limited the development of genetically corrected, autologous iPS cell-based therapies.MethodsWe developed Dystrophic Epidermolysis Bullosa Cell Therapy (DEBCT), a new generation GMP-compatible (cGMP), reproducible, and scalable platform to produce autologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Classic tissue recombination experiments demonstrate that the signal interactions between epithelium and local mesenchyme are essential for tissue morphogenesis and cell fate determination 27 . We and others have demonstrated the significance of integrating supporting cellular signals into human tissue engineering 25,26,28 , reinforcing the importance of detailing the spatial architecture of developing human esophagus. To systematically map the cell types revealed in single cell atlas, we orthogonally performed unbiased Visium spatial transcriptomics (16 sections from 5 timepoints, 5 donors) and high-resolution CODEX (co-detection by indexing) proteomic profiling (48 sections/905,062 cells from 13 timepoints, 15 donors) (Figure 1C, Table S1).…”
Section: A Spatiotemporal Multi-omics Cell Atlas For Human Esophageal...mentioning
confidence: 66%
See 1 more Smart Citation
“…Classic tissue recombination experiments demonstrate that the signal interactions between epithelium and local mesenchyme are essential for tissue morphogenesis and cell fate determination 27 . We and others have demonstrated the significance of integrating supporting cellular signals into human tissue engineering 25,26,28 , reinforcing the importance of detailing the spatial architecture of developing human esophagus. To systematically map the cell types revealed in single cell atlas, we orthogonally performed unbiased Visium spatial transcriptomics (16 sections from 5 timepoints, 5 donors) and high-resolution CODEX (co-detection by indexing) proteomic profiling (48 sections/905,062 cells from 13 timepoints, 15 donors) (Figure 1C, Table S1).…”
Section: A Spatiotemporal Multi-omics Cell Atlas For Human Esophageal...mentioning
confidence: 66%
“…While the epithelial morphogenesis has been documented superficially, the underlying stromal composition and roles in morphogenesis remain unknown. Developmental studies in skin squamous stratified epithelium and our recent work have shown that regional mesodermal morphogenic signals wire the spatialtemporal specific stratification program in surface ectoderm progenitors, and these signals are required in our hPSC-derived skin production for optimal graftability 25,26 . Therefore, to accelerate esophageal mucosa manufacturing, a holistic molecular characterization of the coordinated development of epithelium and stroma is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Also worth noting is the fact that their own variant, LZ3 Cas9, exhibits a differential +1 insertion profile when compared to spCas9 [131]. HiFi Cas9, on the other hand, is already used by many groups in the gene editing field, including several groups working on the correction of the mutations underlying EB [134][135][136][137].…”
Section: Cas9 Variants and Their Impact On Editing Specificitymentioning
confidence: 99%
“… 27 Four gene-edited iPSCs were then differentiated into keratinocytes and fibroblasts and showed C7 restoration. 27 Recently, Neumayer et al 28 developed a method to reprogram EB patient-derived fibroblasts into iPSCs and undertake CRISPR-based correction to generate skin composite grafts. Mouse xenografts showed no tumors and exhibited stable C7 re-expression thus offering promise for future clinical translation.…”
Section: Gene Therapymentioning
confidence: 99%